Value Chain and Digital Pathways for South Nias Robusta Coffee - Ferdinand Tharorogo Wau; Firdaus Laia; Setia Murni Telaumbanua; Survei Halawa; Laura Olivia Putri Sarumaha (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Coffee is a strategic plantation commodity in Indonesia, where regional differentiation and value distribution along the chain determine competitiveness and income capture. Specific Background South Nias Regency possesses favorable agro-climatic conditions for Robusta coffee, yet production, post-harvest handling, and market access remain traditional and weakly documented, resulting in limited recognition as a local commodity. Knowledge Gap Previous studies have largely examined value chain development, digital marketing, or creative economy approaches separately and have focused on established Indonesian coffee origins, leaving emerging regions such as South Nias under-researched within an integrated analytical framework. Aims This study aims to analyze the Ulunoyo South Nias Robusta coffee chain by integrating value chain analysis with consumer evidence and a practical digital marketing roadmap. Results Using a mixed-methods design, the findings show a short, domestically oriented chain dominated by smallholders and a single collector, notable farm–collector price spreads, basic post-harvest practices, and consumer demand concentrated on powder products with a majority willing to pay for premium attributes, particularly taste and origin. Governance patterns indicate market-type coordination with captive features. Novelty The study presents a sequenced, evidence-based pathway that simultaneously links farm practices, mid-chain coordination, and end-market behavior for an under-researched coffee origin. Implications The results suggest actionable upgrading tracks encompassing process standardization, functional movement into roasting and branding, and channel development through minimal digital tools, providing a locally feasible model for strengthening South Nias Robusta coffee within local and national markets. Highlights: Monetary value concentration occurs beyond the farm gate within a short domestic trading structure. Consumer demand prioritizes sensory attributes and shows substantial readiness for premium characteristics. Integrated upgrading routes connect post-harvest practices, branding activities, and online market channels. Keywords: South Nias Robusta Coffee, Value Chain Analysis, Digital Marketing, Consumer Willingness to Pay, Creative Economy